A social analysis of the Red de Protección Social (RPS) in Nicaragua - Adato, Michelle; Roopnaraine, Terry; Álvarez, Fabiola Alvarado; Peña, Leticia Böttel; Castrillo, Gladys Meléndez (International Food Policy Research Institute, 2004)
The Government of Nicaragua‘s program Red de Protección Social (RPS) represents a new approach to providing safety nets for the poorest people in society, a conditional cash-transfer program that has become an important part of poverty alleviation strategy in several countries in Latin America and elsewhere in the world. What is so important about CCTs is that first, they take a systematic approach to assuring a basic income safety net for the poor, rather than relying on more diffuse, indirect process of poverty reduction, e.g. through demand-driven infrastructure programs; and second, they aim to do more than just put short-term cash in people‘s hands—important as this aspect of safety nets is—but also to invest in the long-term human capital of future generations. They achieve this by conditioning cash transfers on participation of households in health and education services, based on the premise that attention to early children health, nutrition and education significantly increases these children‘s chances of climbing out of poverty later in life. In RPS, beneficiaries must attend health education workshops every two months; bring children to prescheduled preventative healthcare appointments and ensure current vaccinations for children between 0-5 years old; ensure an 85 percent school attendance record for children between 7-13, through 4th grade. In return, beneficiaries receive a cash transfer intended for the purchase of food (and improving diet quality); those with eligible school-age children also receive three cash transfers for school attendance, school supplies, and the teacher transfer to be given to the teacher